KORELASI KEMAMPUAN BERPIDATO DENGAN KEMAMPUAN MENULIS TEKS PIDATO SISWA - Yulistio, Didi; Fhitri, Anita (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
. The purpose of this study was to determine the correlation of Speech Ability with the Ability to Write Speech Texts of Class XI Students of SMAN 2 Bengkulu City. This research used correlational method. The research population was all students of class XI of SMAN 2 Bengkulu city with the research sample using purposive sampling technique that is with special consideration only taking students of class XI-E MIPA as many as 30 people. Research design with independent variable (X) speech skills and dependent variable (Y) ability to write speech text. Data collection used speech practice tests and speech text writing tests. The research instruments were (1) instructions and rubrics for writing speech texts including aspects of content, text structure, diction, formal sentences, and mechanics (BI spelling) and (2) rubrics for assessing speech practice including five elements of linguistic aspects and five elements of non-language aspects. The data analysis technique used the average formula for each variable and the product moment correlation formula to test the research hypothesis. The results showed that students' speech skills were categorized as good followed by students' speech text writing skills which were also categorized as good. The alternative hypothesis test results with kk of 0.977 at the 5% significance level or rhit (0.977) > rtabel (0.361) are accepted. That is, there is a positive and significant correlation between Speech Proficiency and Speech Text Writing Ability of Class XI Students of SMAN 2 Bengkulu City. This means that the high value of speech text writing ability occurs because of the high value of students' speech ability or vice versa